Biofilm formation and slime production as virulence determinants among isolates from indwelling devices - Shrestha, Rajani; Nayak, Niranjan; Bhatta, Dharm Raj; Hamal, Deependra; Gokhale, Shishir (Journal of Kathmandu Medical College, 2023)
Background: Biofilm is defined as an assembly of microorganisms which enclosed in a self-produced extracellular matrix principally of polysaccharide material and found in association with indwelling medical devices. This study was designed to determine the biofilm forming ability of isolates from devices associated infection. Objectives: To compare and evaluate biofilm production with the virulence markers like multidrug resistance and slime production. Methods: An analytical observational study was conducted in Manipal Teaching Hospital from 2020 June-2021 May after ethical clearance. A total of 106 clinical isolates were obtained from patients with indwelling medical devices. All bacteria were identified by conventional techniques. Antimicrobial sensitivity testing was performed on Mueller-Hinton agar plates with commercially available antibiotic discs using Kirby Bauer disc diffusion techniques and interpreted as per the guidelines of Clinical and Laboratory Standards Institute (CLSI). Biofilm and slime production were detected by two methods: Tissue culture plate method and Congo Red Agar method. Results: Out of 106 total isolates, 79 (74.5%) isolates were detected in endotracheal tubes (ETTs). Besides, it was observed that 54 (68.3%) of the 79 ETT isolates were biofilm producers. Amongst the isolates, 90.4% (19/21) were Klebsiella species, 64.1% (25/39) Acinetobacter spp., 47.6% (10/21) Pseudomonas spp., and 54.5% (6/11) Staphylococcus aureus were biofilm producers. Conclusion: Biofilm mediated persistence of infection in the nosocomial setting through indwelling devices. Significantly, higher number of the biofilm producers as well as slime producers were multidrug resistant (p-value <0.05).